Pengaruh Literasi Agama Terhadap Pemahaman Siswa Pada Mata Pelajaran PAI Materi Akhlak Di Kelas XI MIPA 2, SMAN 14 Garut - Maria, Anly; Salamah, Aas (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Religious literacy involves placing religious literacy practices within the context of ideology and power relations reflected in literacy artifacts (texts). In this study, religious literacy is specifically examined through instructional materials designed to enhance students' understanding in Islamic Religious Education (PAI), particularly in the area of ethics (akhlak). Understanding is defined as students' ability to grasp the literal messages embedded in communication, interpreting theories using their own language. Each student inherently possesses varying levels of comprehension regarding the subject matter presented, especially in PAI ethics. This research aims to determine: The level of students' understanding in the ethics course in the XI MIPA 2 class at SMAN 14 Garut before intervention. The implementation of religious literacy as instructional material in the ethics course in the XI MIPA 2 class at SMAN 14 Garut. The level of students' understanding in the ethics course in the XI MIPA 2 class at SMAN 14 Garut after the intervention. Thus, the study explores the relationship between the use of religious literacy as instructional material and students' comprehension in the ethics course within PAI. The methodology employed in this research is a quantitative experimental approach, gathering data or information on the observed phenomena. Data collection techniques include distributing test questions to 25 respondents, observation, interviews, and document analysis. Data processing is conducted through statistical data analysis. The results indicate a correlation value of 0.70 between the pre-test and post-test scores in student understanding of the ethics material, which falls within the high correlation range of 0.60 to 0.80. The coefficient value suggests that religious literacy impacts 49% of students' understanding in the ethics material in the XI MIPA 2 class at SMAN 14 Garut, while 51% is influenced by other factors not examined in this study. Additionally, the calculated t-value (4.73) is greater than the t-table value (1.71), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). This means that utilizing religious literacy as instructional material significantly enhances students' comprehension in the PAI ethics course. Keywords: Religious Literacy, Student Understanding, Ethics Education